2018
DOI: 10.1016/j.talanta.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility spectrometer with orthogonal X-Ray source for increased sensitivity

Abstract: Ion mobility spectrometers (IMS) are compact devices for extremely sensitive detection of proton and electron affine volatile compounds down to low ppt concentrations within less than a second. The measuring principle requires ionization of the target analyte. Most IMS employ radioactive electron sources, such as Ni orH. These radioactive materials suffer from legal restrictions limiting the fields of application. Furthermore, the electron emission has a predetermined intensity and cannot be controlled or disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Ion generation is initiated either by electron emission from a radioactive 3 H source (130 MBq) or by radiation from a custom nonradioactive X-ray source (Model XRT-50-2-Rh-0.6-125 by Newton Scientific Inc., Cambridge, Massachusetts, USA). It has been shown, that X-rays can be considered as nonradioactive substitute for the 3 H ionization source, but the Xray source should be placed orthogonally to the axis of the drift tube to avoid any offset current on the detector [14,15]. Ions are injected into the drift region using a field switching shutter as described in [16].…”
Section: Miniaturized Drift Tubementioning
confidence: 99%
“…Ion generation is initiated either by electron emission from a radioactive 3 H source (130 MBq) or by radiation from a custom nonradioactive X-ray source (Model XRT-50-2-Rh-0.6-125 by Newton Scientific Inc., Cambridge, Massachusetts, USA). It has been shown, that X-rays can be considered as nonradioactive substitute for the 3 H ionization source, but the Xray source should be placed orthogonally to the axis of the drift tube to avoid any offset current on the detector [14,15]. Ions are injected into the drift region using a field switching shutter as described in [16].…”
Section: Miniaturized Drift Tubementioning
confidence: 99%
“…Ion mobility spectrometers (IMS) combining atmospheric pressure chemical ionization (APCI) with field switching ion shutters are extremely sensitive trace gas detectors, reaching limits of detection (LoD) in the single digit ppt v range within measurement times of a second. However, depending on the target molecule properties, positive and/or negative ions may form during the ionization process. Thus, analyzing of both ion polarities is required in many applications.…”
mentioning
confidence: 99%
“…Soft x rays between 2.25 and 5 keV were demonstrated with an alternate ion mobility design, the differential ion mobility spectrometer, by Kuklya et al, 9 and ion production was found identical to the widely distributed ion source for IMS, a beta emitter 63 Ni. Other applications with x-ray sources were given by Bunert et al, 10 who used a 4.9 keV x-ray source with an orthogonal installation to avoid secondary consequences of x-ray penetration into the inner volume of the drift tube, and Ahrens et al, 11 who used 3 keV x rays as an alternative for tritium in a miniature IMS drift tube. A design with two 4.9 keV x-ray sources in a tandem arrangement permitted fast switching between multiple reagents in atmospheric pressure chemical ionization mass spectrometry by Rissanen et al 12 Riebe et al 13 used 2.8 keV soft x rays as the APCI ionization source for research of photoionization of explosives and dopants.…”
Section: Introductionmentioning
confidence: 99%